CONTROL OF SCHOOL FACILITIES AND INFRASTRUCTURE PROJECTS OF OGAN KOMERING ILIR REGENCY AND OGAN ILIR REGENCY - Handa Dwi Sanrach; Hikma Dewita; Kristina Sembiring; Pio Ranap Tua Nabiho (University Muhammadiyah Jakarta, 2023)
The project and school infrastructure of Ogan Komering Ilir Regency and Ogan Ilir Regency aims to determine project performance. The analysis was carried out based on completed projects in the aspects of time and cost control using the Earned Value Analysis concept which consists of three indicators, namely BCWS, BCWP and ACWP. The analysis was carried out on time deviations (SV), cost deviations (CV), total budget deviations (BV) and was carried out in weeks (21 weeks). From this deviation analysis, productivity and project performance can be analyzed again, such as the time performance index (SPI) and Cost Performance Index (CPI). Based on Earned Value analysis, the schedule deviation (SV) on the project is 0. This means that in Week 21 the heavy work carried out was completed according to plan. Apart from that, the time performance index on the project is 1 (implementation completed according to schedule), while the cost performance index is 1.03 (1.3 > 1 which means expenditure is lower than planned).